Student's Reading Comprehension as Related to Strategies Used in Reading - Fitri Anna Zila; Ayu Rizky Septiana (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Reading strategies are important things that can affect students' reading comprehension. The use of appropriate strategies can improve reading skills well, while the use of inappropriate strategies can have an impact on poor comprehension. This study describes how students' reading comprehension as related to the strategies used by students using a qualitative method of case study type. Data were collected through interviews, questionnaires, observations, and student ability tests. The results of the analysis show that the right reading strategy can improve students' reading comprehension. Students who use skimming and scanning strategies appropriately show good reading comprehension. In contrast, students who used questioning, global, PROB, and SUP strategies inappropriately showed poor reading comprehension. Nonetheless, it is important to note that students with low performance on certain strategies still have the potential to comprehend the reading as a whole with other reading strategies. This study concludes that the use of appropriate reading strategies can affect reading comprehension